Piezomagnetization of meteorites - Nagata, Takesi; Funaki, Minoru; Dunn, J.R. (1982)
P(論文) The piezo-remanent magnetization (PRM) of Mt. Baldr b (H5-6) and ALH-769 (L6) chondrites and Yamato-74013 diogenite is experimentally demonstrated. J_γ^∥(H_+P_+P_0H_0) of these stony meteorites is approximately proportional to an applied magnetic field, H, when P is kept constant. There is a possibility that the natural remanent magnetization of the two chondrites is due to an acquisition of PRM in a weak magnetic field. Dependence of magnetic susceptibility of a stony meteorite upon applied uniaxial compression and the magnetic susceptibility anisotropy of stony meteorites also are experimentally examined. departmental bulletin paper